Controlling the time evolution of mAb N-linked glycosylation - Part II: Model-based predictions - Villiger, Thomas K; Scibona, Ernesto; Stettler, Matthieu; Broly, Hervé; Morbidelli, Massimo; Soos, Miroslav (Biotechnology progress, 2016)
N-linked glycosylation is known to be a crucial factor for the therapeutic efficacy and safety of monoclonal antibodies (mAbs) and many other glycoproteins. The nontemplate process of glycosylation is influenced by external factors which have to be tightly controlled during the manufacturing process. In order to describe and predict mAb N-linked glycosylation patterns in a CHO-S cell fed-batch process, an existing dynamic mathematical model has been refined and coupled to an unstructured metabolic model. High-throughput cell culture experiments carried out in miniaturized bioreactors in combination with intracellular measurements of nucleotide sugars were used to tune the parameter configuration of the coupled models as a function of extracellular pH, manganese and galactose addition. The proposed modeling framework is able to predict the time evolution of N-linked glycosylation patterns during a fed-batch process as a function of time as well as the manipulated variables. A constant and varying mAb N-linked glycosylation pattern throughout the culture were chosen to demonstrate the predictive capability of the modeling framework, which is able to quantify the interconnected influence of media components and cell culture conditions. Such a model-based evaluation of feeding regimes using high-throughput tools and mathematical models gives rise to a more rational way to control and design cell culture processes with defined glycosylation patterns. © 2016 American Institute of Chemical Engineers Biotechnol. Prog., 32:1135-1148, 2016.
Keywords: Animals; biologické modely; process parameters; CHO buňky; Hydrogen-Ion Concentration; Glycosylation; N-linked glycosylation; Antibodies, Monoclonal; časové faktory; Time Factors; Models, Biological; kultivované buňky; Cricetulus; Cells, Cultured; microbioreactors; glykosylace; monoklonální protilátky; Bioreactors; zvířata; koncentrace vodíkových iontů; media design; bioreaktory; model-based optimization; CHO Cells